2012
DOI: 10.1021/ef300130e
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized-Bed Combustion of Mixtures of Rapeseed Cake and Bark: The Resulting Bed Agglomeration Characteristics

Abstract: The bed agglomeration characteristics resulting from the combustion of 11 mixtures of rapeseed cake and spruce bark were studied in a bench-scale bubbling fluidized-bed reactor (5 kW). The objective was to determine the defluidization temperatures and the prevailing bed agglomeration mechanism as functions of the fuel mixture. Controlled fluidized-bed agglomeration tests were performed for each mixture with quartz sand as the bed material. The total defluidization temperatures and the initial defluidization te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…The abundance of phosphorous in the seed-originating biomass materials like wheat bran, cereal grain and meals was reported previously. 8,[13][14][15] Phosphorus is a vital nutrient for cell division and development of new tissues, which is essential for seeds formation and growth consequently. 14 Therefore, a large amount of phosphorous are found in seeds, cereals, grains, husks and grans.…”
Section: Characterization Of Fuels Additives and Produced Pelletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of phosphorous in the seed-originating biomass materials like wheat bran, cereal grain and meals was reported previously. 8,[13][14][15] Phosphorus is a vital nutrient for cell division and development of new tissues, which is essential for seeds formation and growth consequently. 14 Therefore, a large amount of phosphorous are found in seeds, cereals, grains, husks and grans.…”
Section: Characterization Of Fuels Additives and Produced Pelletsmentioning
confidence: 99%
“…12 A general trend is that large amount of K and/or P can be found in agricultural and food processing wastes, together with other main ash-forming elements like Si and Ca. [13][14][15] Different than woody biomasses, relative concentrations of key ash forming elements (i.e., K, Si, P and Ca) vary significantly for agricultural and food processing wastes. [16][17][18] It was reported that the content of phosphorus in some agricultural wastes is even higher than that of silicon.…”
Section: Introductionmentioning
confidence: 99%
“…However, this fuel ash also contained the significant amounts of calcium and magnesium, which was reported to increase the ash and ash/bed melting temperatures and to reduce the risk of bed agglomeration problem [18,19]. Silica sand (SiO 2 ¼ 99.5 wt%) with solid density z2500 kg/m 3 and particle size 0.3e0.5 mm was used as bed material at the static bed height of 30 cm and to avoid the bed agglomeration, it was replaced every 18 h of use.…”
Section: Fuel and Bed Characteristicsmentioning
confidence: 99%
“…The formation of ash coatings and agglomeration has been subject to numerous studies and there are mechanisms suggested in the literature [17,18,23,26,27,[31][32][33]. An attempt to describe the agglomeration phenomena with a simplified mechanistic model can be found in [34,35] and is used in [36] to explain the agglomeration during co-combustion of bark and rapeseed cake in a fluidized bed, Fig. 1B.…”
Section: Introductionmentioning
confidence: 99%